Discrepency in grade between preoperative biopsy and final specimen in stage I carcinoma endometrium: an institutional review - Kajamohideen, Suhaildeen; Venkitaraman, Balasubramanian; V., Sridevi (International Journal of Research in Medical Sciences, 2019)
Background: Most endometrioid endometrial cancer are well differentiated (Grade I). Grade of the tumor is an important predictor of nodal metastasis and the discordance in histological grade of endometrial cancers between diagnostic biopsy and definitive surgery specimen was analyzed in our Institute. Methods: Around 221 patients diagnosed with carcinoma endometrium between 2006 and 2014 were taken into study. Histologic differentiation of the tumour between diagnostic biopsy and definitive surgery were analysed. All demographic data, tumor factors, follow up and recurrence were recorded. Results: Of the 221 patients taken into consideration for analysis, median age of presentation was 57 years with range between 38-77 years. The overall median body mass index was 27.70kg/m2. 66 % of patients had comorbid illness, with 33% having both diabetes and hypertension. Open staging was performed in 150 patients and laparoscopic staging in 71 patients. Mean duration of surgery was 3.06 hrs in laparoscopic staging and 2.74hrs in open staging. The median tumour size was 4cm.The median number of nodes dissected were 13. Discordance in the grade of tumour between diagnostic biopsy and surgical biopsy were 58.8% of grade 1 tumour, 16.2% of grade 2 tumours and 18.9% of grade 3 tumours. Conclusions: Discrepancies in correlation of the grade of tumour in diagnostic biopsy and tissue obtained at surgery supports the need for surgical staging in all patients.